2014
DOI: 10.2298/gensr1403705k
|View full text |Cite
|
Sign up to set email alerts
|

Parametric stability analyses of multi-environment yield trials in Triticale (xTriticosecale wittmack)

Abstract: One of the main goals of Triticale (xTriticosecale Wittmack) Breeding Program of Turkey is to improve high yielding and stable genotypes across environments. In this study, 16 parametric stability methods were used to evaluate the genotype x environment interaction (GEI) in 9 (4 officially registered varieties and 5 advanced lines) triticale (xTriticosecale Wittmack) genotypes. The genotypes were evaluated for grain yield at 4 different locations for 3 years in rain-fed areas of Turkey. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…3). The findings reported earlier by , Ozer (2014), andGoksoyet al (2019) also support the present results on MY and Pi. In addition, a significant positive rank correlation was observed among all possible pairs of W i 2 ,σ i 2 , θ i , 2021) reported a high correlation between these statistics.…”
Section: Spearman Rank Correlation Among Various Stability Statisticssupporting
confidence: 93%
“…3). The findings reported earlier by , Ozer (2014), andGoksoyet al (2019) also support the present results on MY and Pi. In addition, a significant positive rank correlation was observed among all possible pairs of W i 2 ,σ i 2 , θ i , 2021) reported a high correlation between these statistics.…”
Section: Spearman Rank Correlation Among Various Stability Statisticssupporting
confidence: 93%
“…The results could be presented in the German Plant Cultivar Catalogue [22] and in the official cultivar recommendations at national and regional levels. Both farmers and advisors would have access to this additional and practiced-oriented information regarding the eco-stability of cultivars to support the cultivar-selection process with regard to climate change adaptation [28].…”
Section: Same Importance Of Eco-stability As Additional Informationmentioning
confidence: 99%
“…The genotype x environment interaction accounted for 15.895% of the total variation in our experiment and was significant. The researches of different authors (Gelalcha et al, 2007;Akbarian et al, 2011;Dogan et al, 2011;Lule et al, 2014;Kaya & Ozer, 2014;Kendal et al, 2019;Bocianowski et al, 2021) confirm the significance of the interaction in various studied genotypes and conditions of the environment. Only the results of Dogan et al (2009) did not show significant effect in the triticale lines they investigated both of the genotype and the genotype x environment interaction with regard to yield.…”
Section: Resultsmentioning
confidence: 90%
“…In fact, in our previous research (Stoyanov & Baychev, 2021), the results from the investigated cultivars undoubtedly demonstrated that the lines were with much higher productivity in comparison to the local and world checks. Such values have been rarely reported on the triticale genotypes; they often vary between 1 and 10% from the total variation (Gelalcha et al, 2007;Dogan et al, 2011;Kaya & Ozer, 2014;Kendal et al, 2019), while the effect of the environment may reach up to 98% (Kendal et al, 2019). Obuchowski et al (2010) and Grzesiak et al (2012) have also reported a high effect of the genotype on the yield from triticale.…”
Section: Resultsmentioning
confidence: 96%